2009
DOI: 10.1007/s10875-009-9355-z
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Cells Facilitate the Humoral Immune Response in Patients with Acute Viral Myocarditis

Abstract: It was Th17 cells but not Th2 cells that helped the B cells to produce AHA in AVMC and not until at the late phase of viral myocarditis could Th2 cells play the important role in mediating humoral response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 25 publications
5
49
0
1
Order By: Relevance
“…Besides the proinflammatory effect of Th17 cells, our earlier research suggested that Th17 cells could facilitate the production of autoantibodies in the development of AVMC (5,6). However, the relationship between Th17 cells and CVB3 replication remains unknown in AVMC.…”
mentioning
confidence: 97%
“…Besides the proinflammatory effect of Th17 cells, our earlier research suggested that Th17 cells could facilitate the production of autoantibodies in the development of AVMC (5,6). However, the relationship between Th17 cells and CVB3 replication remains unknown in AVMC.…”
mentioning
confidence: 97%
“…Our previous studies demonstrated that the blockade of the MR blunts the ability of aldosterone to induce Th17 polarization in vitro 22 and MR blockade reduced myocardial fibrosis and enhanced survival of mice with viral myocarditis, a Th17-associated disease. 26,27 Even though IL-17 blockade (protocol 3) ameliorated hypertension, oxidative stress, and fibrosis, we observed that the antihypertensive triple therapy prevented glomerular damage and cardiac hypertrophy in DOCA-salt rats, indicating that development of renal dysfunction and cardiac hypertrophy are blood pressure dependent. The induction of Foxp3 expression in T cells results in a strong reduction of Th17 polarization and blunts the RORγt-induced expression of IL-17 both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 78%
“…Although the role of IL-17A in humoral immunity is not well understood, it has been shown that B cells express IL-17RA (59), whereas Th17 cells (major IL-17A producers) promote antibody production by B cells (60). To test the possible effect of IL-17A in humoral immune responses during WNV infection, we compared WNV-Especific IgM antibody production in WNV-infected Il17a Ϫ/Ϫ and WT mice by ELISA.…”
Section: Figmentioning
confidence: 99%